LITERATURE REVIEW: IMPLEMENTASI SISTEM INFORMASI MANAJEMEN PUSKESMAS DALAM MENUNJANG PELAYANAN REKAM MEDIS DI PUSKESMAS - Gabriela Maruapey (Yayasan Pendidikan Medika Indonesia, 2022)
Background: There is a system called the puskesmas management information system (SIMPUS) to support the implementation of medical record and health information services at community health centre. SIMPUS is an arrangement that provides information to assist the decision-making process in implementing the community health centre management in achieving the its activities target. Purpose: This study aims to investigate the implementation of puskesmas management information system. Methodology: This study was categorized as traditional literature review research that used compare, contrast and criticize techniques. Results: In this implementation of SIMPUS, data were collected using computerized system, then this data were inputted into the application, and processed to produce output in the form of information. The application of SIMPUS had not been fully effective because the information was not relevant to the actual condition. There were several inhibiting factors in implementing SIMPUS, include: the behavior of officers, human resources, public facilities, and software systems. Conclutions: The implementation of SIMPUS still unoptimized. It is recommended that Community Health Centre could provide training and optimize the management function for Head of Community Health Care, such as supervisory function towards officers, in order to enhance the discipline and timely in collecting data to the officers who responsible for SIMPUS.